Воспитание и обучение детей с особыми потребностями в инклюзивной группе детского сада - Тирская, И.А. (My University, 2016)
The article describes the tasks, conditions and methods of inclusive education in preschool organization. Generalization and performance the experience of the collective kinder – garden by introduction system psycho – pedagogical support of inclusion children.
Keywords: inclusion; individualization; tolerant attitude; accompaniment; socialization